Pengembangan Kompetensi Pemandu Desa Wisata dalam Perencanaan Infrastruktur di Pemandian Pijar Jaya Desa Sungai Duren KKN Tematik UIGM - Eltha Hasaelvana; Winie Sapita; M. Haikal; Rizki Dimas Maulana; Hala Haidir; Lesi Hartati (I-Com: Indonesian Community Journal, 2024)
Improving the quality and appeal of tourist destinations, especially in developing villages, requires the development of skills for village tour guides. Through the Thematic Community Service Program (KKN) of Indo Global Mandiri University (UIGM), this training focuses on developing the skills of village tourism guides in infrastructure planning at Pijar Jaya Hot Springs, Sungai Duren Village. The main objective of this activity is to enhance the understanding and skills of village tourism guides regarding effective and sustainable infrastructure planning. This will help the development and management of tourist destinations in a more professional manner. This research uses surveys, preparation, and the implementation of the welcome monument construction. Planning environmentally friendly infrastructure, resource management, and strategies for effectively interacting with tourists. This research concludes that an education and training approach integrated with the local community can effectively enhance the skills of village tourism guides, particularly in terms of planning and managing infrastructure. In addition, the results of this program show that active community participation in infrastructure planning also supports the success of the development of the tourist village.Keywords: Competencies of village tourism guides, infrastructure planning, Pijar Jaya Bathing, Sungai Duren Village, Thematic KKN UIGM.